Soviet Coordinators of International Economic Cooperation in the Eastern Bloc in the Period 1948-1953 - FIŠER, Ondřej (Historia i Świat, 2023)
This article is a discourse on the main trendsetters of international economic cooperation in the Eastern Bloc in the period 1948-1953. Special emphasis is placed on the architects of cooperation between Czechoslovakia and the Soviet Union, since both countries established themselves as economic leaders after the Second World War and, moreover, developed a number of specific close links between their industries. The article focuses on the role of top officials of the Communist Party of the Soviet Union. In addition, the paper also explores the role of Soviet advisors who stewarded the economies of the other Eastern Bloc states, both from Moscow and as seconded delegates directly from the ministries and enterprises of the individual members of the Council for Mutual Economic Assistance.